The nutrition and immunity (nutrIMM) study: protocol for a non-randomized, four-arm parallel-group, controlled feeding trial investigating immune function in obesity and type 2 diabetes - Braga Tibaes, Jenneffer Rayane; Barreto Silva, Maria Inês; Makarowski, Alexander; Cervantes, Paulina Blanco; Richard, Caroline (Frontiers in Nutrition, 2023)
Introduction: Individuals with obesity and/or type 2 diabetes are at higher risk of infection and have worse prognoses compared to healthy individuals. Several factors may influence immune responses in this population, including high adiposity, hyperglycemia, and unhealthy dietary habits. However, there is insufficient data on the independent or clustered contribution of these factors to obesity-related immune dysfunction, especially accounting for dietary intake. This study aims to establish the independent contribution of obesity and hyperglycemia to immune dysfunction independent of diet in adults with and without obesity with or without type 2 diabetes. Methods: The Nutrition and Immunity (nutrIMM) study is a single-centre, non-randomized, four-arm, parallel-group, controlled feeding trial.It will enroll adults without obesity (Lean-NG) and with obesity and three metabolic phenotypes of normoglycemia, glucose intolerance, and type 2 diabetes. Participants will be assigned to one of four groups and will consume a standard North American-type diet for four weeks. The primary outcomes are plasma concentration of C-reactive protein and concentration of ex-vivo interleukin-2 secreted upon stimulation of T cells with phytohemagglutinin. Discussion: This will be the first controlled feeding study examining the contribution of obesity, hyperglycemia, and diet on systemic inflammation, immune cell phenotype, and function in adults of both sexes. Results of this clinical trial can ultimately be used to develop personalized dietary strategies to optimize immune function in individuals with obesity with different immune and metabolic profiles.